Ultra-sensitive quantification of the therapeutic cyclic peptide bremelanotide utilizing UHPLC-MS/MS for evaluation of its oral plasma pharmacokinetics - Sauter, Max; Uhl, Philipp; Burhenne, Jürgen; Haefeli, Walter E. (Journal of pharmaceutical and biomedical analysis, 2020)
Bremelanotide (Vyleesi®), a cyclic heptapeptide, was recently approved for the subcutaneous treatment of premenopausal hypoactive sexual desire disorder. To foster the development of alternative routes of administration, we aimed at determining the oral plasma pharmacokinetics of bremelanotide in beagle dogs. Therefore, we established a UHPLC-MS/MS assay with an LLOQ of 10 pg/mL (9.8 pM) using 100 μL of plasma and validated it according to the guidelines of the US Food and Drug Administration and the European Medicines Agency. Bremelanotide was isolated from plasma by protein precipitation and quantification was performed with positive heated ESI MS/MS in the SRM mode. The calibrated concentration range of 10−10,000 pg/mL was linear showing correlation coefficients > 0.99. In the calibrated range, interday and intraday accuracy ranged from 88.9-100.0 % with corresponding precision < 8 %. Accuracy at the LLOQ ranged from 93.6-100.8 % with corresponding precision < 11 %. Because of the validity of a dilution QC that showed accurate quantification of 10-fold diluted plasma samples (accuracy 99.4 %, precision < 6 %), the assay is suitable for bremelanotide quantification in its effective concentration range up to 100,000 pg/mL. The ultra-sensitive assay was applied to the quantification of bremelanotide plasma concentrations after oral administration to beagle dogs, which indicated minimal oral absorption.
Gesehen am 15.07.2020